Konsepsi Ketatanegaraan Kahar Muzakkar - Bakar, Abu (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Abstract: this article explains the political thought of Kahar Muzakkar. Kahar Muzakkar proclaimed his Islamic state with the name of Republik Persatuan Islam Indonesia (RPII) on 14 of May 1962 which is a realization of his Islamic political thought. Kahar Muzakkar wanted a federal state and positioned sharia as the state foundation. In addition to sharia, Kahar Muzakkar viewed that social justice and democracy were potential concepts that workable for his Islamic federal state. Concerning executive system, he opted for presidential system in which his Islamic federal state was to be led by a president directly elected by people with members of cabinet. Legislative body was also to be formed which would consist of Nation Assembly and the senate. Similar arrangement would be applied for states. Kahar Muzakkar believed that this model would save human civilization. He called this as Demokrasi Sejati in which the ultimate authority is God. God’s law is applicable for all aspects of life as has been revealed in the Quran and Hadith Key words: kahar Muzakkar, Islamic Political Thought, Demokrasi Sejati